Common Variable Immunodeficiency as the initial presentation of Dyskeratosis Congenita - Allenspach, Eric J. (J Allergy Clin Immunol, 2013)
We present a case highlighting the clinical overlap between Common Variable Immunodeficiency (CVID) and Dyskeratosis Congenita (DC). It demonstrates that DC may initially present as an isolated humoral immunodeficiency resembling CVID.